Analisis Dinamika Indsutri Konveksi di Aceh Barat : Tantangan dan Peluang - Sahirman, Sahirman (Teewan Journal Solutions, 2025)
The convection industry in West Aceh has a significant role in the local economy by utilizing the potential of raw materials and local culture. This study analyzes the challenges and opportunities faced by the industry, using a qualitative approach with in-depth interviews with business owners. The research results show that this industry faces obstacles in the form of limited capital, lack of skilled labor, and less than optimal marketing strategies. However, there are great opportunities through the use of digital technology, collaboration with creative communities, and sustainability trends. SWOT analysis identifies strengths in the form of unique products and growing markets, as well as weaknesses such as dependence on certain raw materials. Recommendations include product diversification, improving digital marketing, and strengthening brand identity to increase competitiveness. Implementation of this strategy is expected to support local economic growth and improve the welfare of the people of West Aceh.